Stability constants and thermodynamic parameters of cadmium complexes with sulfonamides and cephapirin - Parihar, Malkhan Singh; Khan, Farid (Eclética Química, 2008)
Stability constant (log 􀁠) and thermodynamic parameters of Cd2+ complexes with sulfonamide and cephapirin were determined by Polarographic technique at pH = 7.30 ± 0.01 and μ = 1.0 M KNO3 at 250°C. The sulfonamides were sulfadiazine, sulfisoxazole, sulfamethaxazole, sulfamethazine, sulfathiazole, sulfacetamide and sulfanilamide used as primary ligands and cephapirin as secondary ligand. Cd2+ formed 1:1:1, 1:2:1 and 1:1:2 complexes. The nature of electrode processes were reversible and diffusion controlled. The stability constants and thermodynamic parameters (􀂨G, 􀂨H and 􀂨S) were determined. The formation of the metal complexes has been found to be spontaneous, exothermic in nature, and entropically unfavourable at higher temperature.